Preaching to the Choir: Turning Anger Into Engagement at Urban Community Colleges - Schwartz, Jesse W. (Radical Teacher, 2018)
In the wake of the election, I attempt to channel my students’ understandable anger, fear, and rage into activism (broadly concieved) outside the classroom.